ACCIDENT ANALYSIS ON IPOH-LUMUT HIGHWAY - Bin Mohd Hawari , Muhammad Hanif (Universiti Teknologi PETRONAS, 2018)
Malaysia is experiencing a rapid growth of economy and population. As the population grows, the numbers of vehicles used on the road will also increasing. Too much vehicles on the road causing lots of accidents and black spot are will exist. The Ipoh-Lumut Highway route is always busy especially on peak hour. The traffic is varying from motorcycle to lorry. The existence of these large vehicles and road construction along the road is the prone to cause accident. The objectives of this study are to identify cause of accident at identified accident prone area along Ipoh-Lumut Highway particularly at Batu Gajah and Perak Tengah district and to propose a mitigation measures for road accident problem. It will be focused on factors causing the accident, existed accident prone area along the route and solution to reduce and eliminate the black spot area and accident numbers. The methods that will be use in this study are the survey based methods such as questionnaires and interviews as well as data collection from police department and spot speed study. The result will be presented in forms of tables, charts and graphs.